2019
DOI: 10.1038/s41597-019-0198-z
|View full text |Cite
|
Sign up to set email alerts
|

ColPortal, an integrative multiomic platform for analysing epigenetic interactions in colorectal cancer

Abstract: Colorectal cancer (CRC) is the third leading cause of cancer mortality worldwide. Different pathological pathways and molecular drivers have been described and some of the associated markers are used to select effective anti-neoplastic therapy. More recent evidence points to a causal role of microbiota and altered microRNA expression in CRC carcinogenesis, but their relationship with pathological drivers or molecular phenotypes is not clearly established. Joint analysis of clinical and omics data can help clar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“… Name Type Omics content Link Species Answer ALS [7] Repository whole-genome sequencing, RNA transcriptomics, ATAC-sequencing, proteomics. Also: deep clinical data, including fine motor activity, speech, breathing and linguistics/cognition https://dataportal.answerals.org/ Human Fibromine [8] Database transcriptomics and proteomics http://www.fibromine.com/Fibromine/ Human/ Mouse DevOmics [9] Database normalized gene expression, DNA methylation, histone modifications (H3K4me3, H3K9me3, H3K27me3, H3K27ac), chromatin accessibility and 3D chromatin architecture profiles of human and mouse early embryos spanning six developmental stages http://devomics.cn Human/ Mouse The Cancer Genome Atlas (TCGA) [10] Repository genomics, epigenomics, transcriptomics, proteomics https://portal.gdc.cancer.gov/ Human jMorp [11] Database/ Repository genomics, methylomics, transcriptomics, and metabolomics https://jmorp.megabank.tohoku.ac.jp/ Human DriverDBv3 [12] Database somatic mutation, RNA expression, miRNA expression, methylation, copy number variation and clinical data in addition to annotation bases http://driverdb.tms.cmu.edu.tw/ Human The Personal Genome Project-UK [83] Repository DNA methylation (bisulfite sequencing), whole genome sequencing, transcriptomics https://www.personalgenomes.org.uk/ Human STATegra [13] Repository RNA-seq, microRNA-seq, ChIP-seq, RRBS, Dnase-seq, ATAC-seq, scRNA-seq, scATAC-seq, proteomics, metabolomics https://opendata.lifebit.ai/table/stategra Mouse ColPortal [14] Repository Mehylation 450 k arrays, 16 S sequencing, expression arrays, microRNA arrays https://colportal.imib.es/ Human The Omics Discovery Index [15] Knowledge dis...…”
Section: Methodsmentioning
confidence: 99%
“… Name Type Omics content Link Species Answer ALS [7] Repository whole-genome sequencing, RNA transcriptomics, ATAC-sequencing, proteomics. Also: deep clinical data, including fine motor activity, speech, breathing and linguistics/cognition https://dataportal.answerals.org/ Human Fibromine [8] Database transcriptomics and proteomics http://www.fibromine.com/Fibromine/ Human/ Mouse DevOmics [9] Database normalized gene expression, DNA methylation, histone modifications (H3K4me3, H3K9me3, H3K27me3, H3K27ac), chromatin accessibility and 3D chromatin architecture profiles of human and mouse early embryos spanning six developmental stages http://devomics.cn Human/ Mouse The Cancer Genome Atlas (TCGA) [10] Repository genomics, epigenomics, transcriptomics, proteomics https://portal.gdc.cancer.gov/ Human jMorp [11] Database/ Repository genomics, methylomics, transcriptomics, and metabolomics https://jmorp.megabank.tohoku.ac.jp/ Human DriverDBv3 [12] Database somatic mutation, RNA expression, miRNA expression, methylation, copy number variation and clinical data in addition to annotation bases http://driverdb.tms.cmu.edu.tw/ Human The Personal Genome Project-UK [83] Repository DNA methylation (bisulfite sequencing), whole genome sequencing, transcriptomics https://www.personalgenomes.org.uk/ Human STATegra [13] Repository RNA-seq, microRNA-seq, ChIP-seq, RRBS, Dnase-seq, ATAC-seq, scRNA-seq, scATAC-seq, proteomics, metabolomics https://opendata.lifebit.ai/table/stategra Mouse ColPortal [14] Repository Mehylation 450 k arrays, 16 S sequencing, expression arrays, microRNA arrays https://colportal.imib.es/ Human The Omics Discovery Index [15] Knowledge dis...…”
Section: Methodsmentioning
confidence: 99%
“…The clinical and pathological characteristics of the study patients were reported previously [13][14][15][16][17]. This study was approved by the Local Ethical Boards from participating hospitals (Ref: PI12-01232), in agreement with the ethical principles laid down in the 1964 Declaration of Helsinki.…”
Section: Patients and Tumor Samplesmentioning
confidence: 99%
“…High-throughput data from our series are fully accessible through Colportal (www. colportal.imib.es, accessed on 7 June 2021), an online integrated platform [16].…”
Section: Treatment With Bisulfite and Dna Methylation Assaymentioning
confidence: 99%
“…Currently, there are many multiomics-based templates that can be recruited as references for use in TCM and microbiota related studies. For instance, a functional analysis of the gut microbiota ecosystem for better understanding inflammatory bowel disease (IBD) (Lloyd-Price et al, 2019 ), while the modified ColPortal platform (Esteban-Gil et al, 2019 ) integrates multiomics studies to understand the relationship between the microbiota and metabolomics in inflammatory bowel disease (IBS) disease model (Liu et al, 2019b ). The pipelines described here have the potential to identify novel TCM-based herbal prebiotics, probiotics, and postbiotics for treatment of disease.…”
Section: Microbiota-based Integrated Multiomics Study-the Next Generation Tcm Herbal Researchmentioning
confidence: 99%